PEMBERDAYAAN INDUSTRI KECIL KERIPIK PISANG DALAM UPAYA MENUJU INDUSTRI MANDIRI - Pudjihastuti, Isti; Supriyo, Edy; Hartati, Retno (Gema Teknologi, 2011)
IstiPudjihastuti, Edy Supriyo, Retno Hartati, in this paper explain that the development of micro industries, in banana chip  micro industry to the  member of group which is culinary enterprise Pemalang speciallized is give suitable solution to  consument for giving natural culinary with high nutrition value independently and cheap. The development of micro  industries is circular activity that consist of briefing about the use of gelatse system in banana chip production by naturally and independently, the suitable tachnique of banana chip production, production of furnace completely by steack as pilot plan, assitancy when the producer makes snack in gelatse system. Moreover, the taste of snack more delicious, the market bigger.   Key words: micro industries banana chip